THE IMPACT OF ZAKAT ON POVERTY LEVELS IN PADANG CITY BASED ON THE CIBEST MODEL - Rozalinda Rozalinda; Ainul Ikhsan (Imara: JURNAL RISET EKONOMI ISLAM, 2022)
This study aims to analyze the impact of zakat on the level of poverty in Padang city based on the CIBEST perspective. The methods used in this study were interviews and questionnaires. The data analysis technique used is the CIBEST model. The results of the CIBEST Index analysis for Padang city show that 53.25% of families live in prosperous conditions, that is, they are materially and spiritually capable. 23.625% of families are in conditions of material poverty, as much as 14% in conditions of spiritual poverty, and 9,125% are in conditions of absolute poverty, which is materially and spiritually poor. Through zakat, the poor can fulfill their rights to material needs. In addition, empowering the poor through a perspective on poverty. Changing the people's mindset towards poverty is the main spirit of making changes towards a better life.